Classification of n-th order limit language in formal language classes - Siti Hajar, Mohd Khairuddin; Muhammad Azrin, Ahmad; Mohd Sham, Mohamad (Semarak Ilmu Publishing, 2025)
The study of splicing systems and their language has grown rapidly since Paun developed a splicing system known as a regular splicing scheme that produces a regular language. Since then, the researchers have been eager to classify the splicing language into certain classes in the Chomsky hierarchy, such as context-free language, contextsensitive language and recursive enumerable language. Previously, the study on the nth order limit language was conducted from the biological perspective to the limit language produced. Still, no research has been done from the generation of language point of view. This research presents a generalization on the type of classes of the formal language, the n-th order limit language. The cases to obtain the n-th order limit language are revisited and used to obtain the types of language classes according to the Chomsky hierarchy produced by the n-th order limit language.